Answer:
Check pdf
Step-by-step explanation:
Answer:
2nd one
Step-by-step explanation:
you first plug (substitute) in y
-3x - 3(-5x-17)=3
then distribute
-3x+15x+51=3
now combine like terms
12x+51=3
subtract to get 12x by itself
12x=3-51 or 12x=-48
lastly divide by 12 to find x
12x/12=-48/12
x=-4
now find y by plugging x into the other equation
y=-5(-4)-17
y=3
(-4,3)
2 3/4 divided by 1/4
is
2 3/4 multiplied by 4/1
which is (2+3/4)*4 = 2*4 + 3/4*4 = 8+3 =<em>11</em>
Answer:
g(x) = (x + 2)^2 + 1
Step-by-step explanation:
From the graph/image that you have provided said translated shift of
f(x) -> g(x)
f(x) = x^2 , g(x) = a(x -h)^2 +k
h is shift right/left
k is shift up/down.
It appears that the shift is left 2 and up 1.
h = -2 and k = 1
g(x) = (x - (-2))^2 +1
g(x) = (x + 2)^2 + 1